2012
DOI: 10.1007/s10194-012-0489-7
|View full text |Cite
|
Sign up to set email alerts
|

Identified risk factors and adolescents’ beliefs about triggers for headaches: results from a cross-sectional study

Abstract: Although there are few studies on adolescents’ beliefs about triggers of headache, none of these compared the associations between perceived and observed triggers. This study aimed at comparing the prevalence of self-perceived and observed risk factors for headache among adolescents. Adolescents from the 10th and 11th grades of high schools answered questionnaires on their headaches and on potential risk factors regarding lifestyle, stress and muscle pain. Individuals reporting to have experienced headache in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Moreover, the prevalence of chronic headache was closely related to the average daily study time, extracurricular learning tasks, and stress received from parents, classmates, and teachers. The reason may be that heavy academic pressure induces an increase in risk factors for headaches (elevated levels of mental stress, lack of sleep, and less exercise) [ 24 ] and changes in adolescents’ living habits (smoking, alcohol and coffee consumption), perhaps promoting the prevalence of chronic headache nonspecifically [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prevalence of chronic headache was closely related to the average daily study time, extracurricular learning tasks, and stress received from parents, classmates, and teachers. The reason may be that heavy academic pressure induces an increase in risk factors for headaches (elevated levels of mental stress, lack of sleep, and less exercise) [ 24 ] and changes in adolescents’ living habits (smoking, alcohol and coffee consumption), perhaps promoting the prevalence of chronic headache nonspecifically [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting approach to the question “does alcohol trigger headache” is the study of adolescents' beliefs regarding headache triggers . Students in the 10th and 11th grade in high school were given questionnaires about headache, lifestyle, risk factors, stress, and muscle pain.…”
Section: Review Of Studies With Discussion Of Important Questions Andmentioning
confidence: 99%
“…Those who were previously unaware of the preventable risk factors for headache would be especially likely to benefit from receiving this information. Indeed, it has been shown that adolescents with headache are actually not aware of many of these risk factors .…”
Section: Introductionmentioning
confidence: 99%